Color Recognition Educational Game using Fisher-Yates for Early Childhood Potential Development - Muhammad Farhan Mahesa Ijlal; Umi Chotijah (P3M Politeknik Negeri Bengkalis, 2022)
To continue basic education, it is necessary to develop potential abilities by learning color recognition in early childhood. However, learning in schools today still uses boring conventional learning methods. Based on these problems, there is a need for an introductory educational game that can be easily used and carried anywhere, anytime by applying the Fisher-Yates shuffle algorithm. The aim is that educational games are not monotonous and boring to play. In this study, in addition to using the Fisher-Yates algorithm, we use the Multimedia Development Life Cycle (MDLC) as the system development method. The results of tests performed using black box testing are as expected. Therefore, this educational game can be used by parents and educators as an alternative to traditional learning tools to further develop early childhood potential in preparation for basic education.